Differences in cutaneous melanoma survival between the 7th and 8th edition of the American Joint Committee on Cancer (AJCC). A multicentric population-based study. (March 2021) - Barreiro-Capurro, Alicia; Andrés-Lencina, Juan J.; Podlipnik, Sebastian; Carrera, Cristina; Requena, Celia; Manrique-Silva, Esperanza; Quaglino, Pietro; Tonella, Luca; Jaka, Ane; Richarz, Nina; Rodríguez-Peralto, José L.; Ortiz, Pablo; et al.
Abstract: Background: The 8th edition of the AJCC manual for melanoma includes many changes leading to major substage migrations, which could lead to important clinical reassessments. Objectives: To evaluate the differences and prognostic value of the 8th AJCC classification in comparison with the 7th edition. Methods: Clinical and histopathological data were retrieved from five melanoma referral centers including 7815 melanoma patients diagnosed between January 1998 and December 2018. All patients were reclassified and compared using the 7th and 8th classifications of the AJCC. Sankey plots were used to evaluate the migration of patients between the different versions. The primary outcome was overall survival (OS), and curves based on the Kaplan-Meier method were used to investigate survival differences between the 7th and 8th editions. Results: The number of patients classified as stages IB, IIIA, and IIIB decreased while the patients classified as stages IA and IIIC increased notably. Migration analysis showed that many patients in group I were understaged whereas a significant percentage of patients in group III were upstaged. Indirect OS analysis showed a loss in the linearity in the AJCC 8th edition and the groups tended to overlap. Direct OS analysis between groups and versions of the AJCC showed a better prognosis within the new stage III patients, with no effect on those in stages I and II. Conclusion: The 8th AJCC edition represents an important change in the classification of patients. We observe that the main migratory changes occur in stage I and III, that severity linearity is lost and groups overlap, and that a more advanced stage does not mean a worse prognosis. Highlights: AJCC 8th includes major changes with clinical implications, especially in stage III. AJCC 8th gives more importance to Breslow index than lymph node involvement. AJCC 8th stages IIIA and IIIB have a better prognosis than IIA or IIB, respectively More advanced AJCC 8th stages do not necessarily translate into a worse prognosis